A roadmap for improving representation in clinical trials - Amanda F. Petrik; Nora B. Henrikson; Gloria D. Coronado; Erin Keast; Matthew P. Banegas (Contemporary Clinical Trials Communications)
Clinical trials continue to struggle with recruiting diverse participants that include historically underrepresented and minoritized patients, who are typically patients in non-white racial and ethnic groups and have low income (Medicaid). Enrolling diverse participants will benefit the health sciences by providing more generalizable findings. The Cancer Financial Experience project (CAFÉ) study sought to improve financial distress by providing financial navigation for newly diagnosed cancer patients, and intentionally recruited diverse participants. All diverse participants consented at slightly higher rates than non-diverse participants (21.3 % vs. 20.1 %). Spanish-speaking patients consented at a much higher rate than non-Spanish speakers (36.4 % vs. 20.2 % respectively). Here we discuss how we increased our recruitment of diverse participants. Obtaining diverse participation is achievable and will provide more meaningful findings.